Media consumption of Japanese popular culture among Malaysian young adults - Yamato, Eriko (2011)
The purpose of this study was to understand the media consumption experiences of Japanese popular culture among Malaysians. Such a study is important in order to understand the consequence of the consumption of foreign cultural products since the development of information communication technology has brought changes to the consumption styles of media entertainment, especially among the younger generation. The hermeneutic phenomenological approach, a qualitative research methodology, was employed in this study. This approach was considered the most appropriate for describing and understanding individual media consumption experiences in a particular context. Twelve Malaysian young adults were selected by criterion and snowball sampling techniques. In-depth interviews, which lasted between fifty minutes to three hours, were conducted by this researcher. Each interview was recorded, transcribed verbatim, and analyzed via thematic analysis. The other documents related to the production, representation, identity and regulation of Japanese popular culture were obtained as supporting data from both Japan and Malaysia.The findings from this study provide insights into the consumption process, which constitutes four components: engagement, accumulation, decoding, and appropriation. The component of engagement was described in relation to technological development and free distribution through the Internet, which remains unregulated. The component of accumulation was found to be an important part of media consumption in developing the young Malaysian consumer’s mindset towards specific formats, genres or products from Japan. Accumulated consumption experiences of cultural products resulted in different outcomes from the decoding of media texts. The findings also reveal that the participants considered a part of the texts as 'foreignness’ or “Japanese-ness’ according to their social positions. While the participants expected to find a sophisticated depiction of human beings in the products that they would reflect on or relate to, they also developed their own ways of thinking during media consumption. As part of the media consumption of Japanese popular culture in Malaysia, the findings also indicate that a new identity, ‘otaku identity,’ has emerged through the participants’ sharing activities of Japanese popular culture among online fans and other Malaysians. Japanese popular culture can be appropriated as part of the participants’ own lifestyle through accumulative consumption experiences. It can even become a basis for establishing good companionship with other people or having an impelling motive to determine their actions in the near future. This study concludes that the media consumption of Japanese popular culture is fundamentally shaped by an individual’s capacity to handle the latest information technology, especially the Internet. The contents of Japanese popular cultural products are crucial. Without a sophisticated depiction of ‘an essential human aspect’ to which young Malaysians could relate, Japanese popular culture would not be well liked. The depiction of human aspects in the products may provide some sort of valuable life lessons for young Malaysians despite the differences that exist between the lifestyles of Japanese and Malaysians.